Oral piercing is a new challenge in the dentistry. - A. V. Samoilenko; V. Yu. Orishchenko; T. N. Strelchenia; O. V. Strelchenia (Medičnì Perspektivi)
The number of the young adults undergoing oral piercing is increasing worldwide. Oral piercing leads to numerous complications, and it is possible that the incidence of complications may increase as the prevalence of oral piercing rises in Ukraine. However, not everyone is aware of its potential risks, local and systemic complications shortly after, or long after the piercing procedure. Dentists should educate patients with oral piercing or those who plan to have this type of body art performed about potential side effects and possible oral, dental, and systemic complications. However, data related to these complications in Ukrainian literature are limited. The purpose of this study – to assess the potential complications of the oral piercing; and to analyze awareness about the actual health risks linked to the practice of oral piercing by dental students. This study includes 37 cases of oral piercing in 36 young women attending the department of therapeutic dentistry of Dnipropetrovsk medical academy with and without complaints. The average subjects age was 22,3 years. Patients were examined clinically and radiographically. 200 students of Dnipropetrovsk medical academy answered a questionnaire about oral piercing knowledge. Immediate complications of oral piercing included pain (58.3% of cases), oedema (47,2%) and bleeding (11.1%) as the most representative. Prolong time of piercing wearing is associated with a greater prevalence of complications. Dental fractures or fissures (35,1%), gingival recession (29,7%) and mucosal atrophy (21,6%) are the most representative. The accumulation of dental plaque and calculus on piercing elements (43,2%) was an additional risk of infection. The results of the survey showed a high level (85,4%) of awareness of dental students about local oral piercing risks. At the same time, dental students (50,6%)  are not sufficiently aware of the risk of piercing on developing systemic complications. Approximately 60% of dental students do not have a negative attitude towards the new practice of oral piercing.